Achalasia Diagnosis and Treatment - Fisichella, P. Marco; Herbella, Fernando A. M.; Patti, Marco G. (Springer International Publishing : Imprint: Springer, 2016)
This comprehensive  book covers the diagnosis and treatment of esophageal achalasia. The successful management of patients with this disease, whose treatment can be complex and usually performed in specialized tertiary-care centres, is described by internationally renowned authors. Detailed operations and current diagnostic and management strategies are discussed, giving the reader expert knowledge in specific aspects of Achalasia.   Achalasia: Diagnosis and Treatment is ideal for residents, fellows and specialists in both general and thoracic surgical disciplines as well as in gastroenterology.